2017
DOI: 10.1016/j.acra.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Cyst Versus Solid Diagnosis in the Breast Using Quantitative Transmission (QT) Ultrasound

Abstract: Rational and ObjectivesThis study aims to evaluate the diagnostic utility of breast imaging using transmission ultrasound. We present readers’ accuracy in determining whether a breast lesion is a cyst versus a solid using transmission ultrasound as an adjunct to mammography.Materials and MethodsThis retrospective multi-reader, multi-case receiver operating characteristic study included 37 lesions seen on mammography and transmission ultrasound. Cyst cases were confirmed as cysts using their appearance on handh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
(19 reference statements)
0
22
0
Order By: Relevance
“…The primary application of this technology has so far been in breast imaging as demonstrated by our previous work . The performance characteristics described above suggest that the QT scanner can provide high‐resolution, high fidelity, multimodality imaging of the breast tissue.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The primary application of this technology has so far been in breast imaging as demonstrated by our previous work . The performance characteristics described above suggest that the QT scanner can provide high‐resolution, high fidelity, multimodality imaging of the breast tissue.…”
Section: Resultsmentioning
confidence: 95%
“…Medical Physics, 45 (7), July 2018 work. 21,25,26 The performance characteristics described above suggest that the QT scanner can provide high-resolution, high fidelity, multimodality imaging of the breast tissue. A representative montage of coregistered sets of images of the whole breast are shown in Figs.…”
Section: Phantom#mentioning
confidence: 99%
“…Using a system combining transmission and reflection, 28 André et al were able to differentiate fibroadenoma (n = 11) from carcinoma (n = 5) with a specificity of 81.8% and sensitivity of 100%. Using a similar system, Iuanow et al 44 demonstrated differentiation of cysts from solid lesions. Three-dimensional multimodal US tomography combines multiple acoustic parameters into a composite index and has shown the capacity to distinguish malignant lesions from healthy tissue as well as from benign lesions and to detect small breast lesions.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the speed of sound, as measured by QT ultrasound ® , can both define tissue types and distinguish cystic from solid masses with high specificity in a clinical setting (21, 22). Traditional reflection ultrasound imaging of cysts reveals either an anechoic interior (no internal reflecting elements visible) for simple cysts or varying degrees of internal reflecting elements visible for complicated or complex cysts.…”
Section: Introductionmentioning
confidence: 99%
“…The current prospective study was an extension of our retrospective investigation into the specificity of the speed of sound in transmission ultrasound of the breast for determining the presence of cystic or solid masse. Additionally, it was done to further clarify the radiologist’s interpretation of cysts with high speed foci observed by transmission ultrasound (22). …”
Section: Introductionmentioning
confidence: 99%